2020
DOI: 10.1177/0265532219898380
|View full text |Cite
|
Sign up to set email alerts
|

Predicting L2 reading proficiency with modalities of vocabulary knowledge: A bootstrapping approach

Abstract: Vocabulary’s relationship to reading proficiency is frequently cited as a justification for the assessment of L2 written receptive vocabulary knowledge. However, to date, there has been relatively little research regarding which modalities of vocabulary knowledge have the strongest correlations to reading proficiency, and observed differences have often been statistically non-significant. The present research employs a bootstrapping approach to reach a clearer understanding of relationships between various mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 38 publications
3
102
0
Order By: Relevance
“…3 https://www.psyctc.org/stats/R/CI_correln1.html; http://vassarstats.net/rho.html Future research should consider using the abovementioned three methods, especially CIs, for comparing previous studies. Additionally, other methods that would provide more precise estimates would be (a) a bootstrapping method (McLean et al, 2020), which is useful when primary data are available, and (b) meta-analysis, which can systematically integrate previous studies while taking sample size and measurement error into account (e.g., Plonsky and Oswald, 2015;In'nami et al, 2020). When researchers obtain a matrix of meta-analyzed correlation coefficients through (b), they can more rigorously examine relationships of size and depth using meta-analytic SEM (Cheung, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 https://www.psyctc.org/stats/R/CI_correln1.html; http://vassarstats.net/rho.html Future research should consider using the abovementioned three methods, especially CIs, for comparing previous studies. Additionally, other methods that would provide more precise estimates would be (a) a bootstrapping method (McLean et al, 2020), which is useful when primary data are available, and (b) meta-analysis, which can systematically integrate previous studies while taking sample size and measurement error into account (e.g., Plonsky and Oswald, 2015;In'nami et al, 2020). When researchers obtain a matrix of meta-analyzed correlation coefficients through (b), they can more rigorously examine relationships of size and depth using meta-analytic SEM (Cheung, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The following shows a sample item from the Vocabulary Size Test Beglar, 2007, JALT2007, p. 2), in which test takers are asked to select the most appropriate meaning of the written target word out of four written choices. While the form-meaning association appears relatively simple to define and assess, research has shown that it is not: Size test scores are affected not only by the intended test construct but also by various factors such as differences in item formats and test takers' test-taking strategies (Gyllstad et al, 2015;Kremmel and Schmitt, 2016;McLean et al, 2020).…”
Section: Measuring Size and Depthmentioning
confidence: 99%
“…Receptive knowledge of the first 3,000 word families has been shown to account for 52% of the variance of Chinese learners’ International English Language Testing System (IELTS) listening scores (Matthews & Cheng, 2015). Additionally, vocabulary knowledge predicted between 38% and 61% of Test of English for International Communication (TOEIC) reading performance depending on the modality of the vocabulary testing and number of test items (McLean et al., 2020). To summarize, research has repeatedly emphasized the relationship between L2 vocabulary knowledge and proficiency across domains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite its importance, vocabulary acquisition, and in turn L2 IVA, has yet to emerge as a clearly defined construct within which consensus has been reached (Schmitt, 2019). This lack of consensus notwithstanding, Nation's (2013) conceptualization of vocabulary knowledge as a multidimensional construct has been one of the most consistently referenced vocabulary knowledge frameworks (e.g., Kremmel & Schmitt, 2016; McLean et al., 2020). In the present study, Nation's framework was utilized to identify what vocabulary was and what a vocabulary acquisition intervention entails.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation